Millennials and the Sandwich Generation: The Challenge of Adapting Self-Identity Across Time - Engine Kubota; Anis Nur Faizah MS; Sandya Mahendra; Agusti Prayoga; Ulfah Dwi Rahmawati (UM Purwokerto Press, 2022)
Nowadays, the term millennial has been heard very often. Millennials or Generation Y are the generation born in the 1980s - early 2000s. At this time, the millennial generation has an age range of 25-40 years and is in the position of the sandwich generation. The sandwich generation itself is the people who are squeezed between the demands of two generations at once, namely parents and children plus the demands of their own life. The sandwich generation now carries a fairly heavy burden considering their lifetimes that have passed the generational transition line which is quite extreme. This study aims: 1) To know the definition of millennials and the sandwich generation in depth. 2) Studying more about the role of millennials who are also the sandwich generation. 3) Knowing the adaptation pattern of the millennial generation and the sandwich generation in the industrial 4.0 era. And this writing uses a descriptive qualitative research methodology by using many data variables that are appropriate in order to produce directed and accountable writing. As technology is developing, everything is moving fast. Likewise, the current generation must adapt to conditions that are far different from the early life they lived. So that this significant difference affects many social aspects in terms of the intergenerational relationship which then gives birth to a mindset and parenting pattern that is qualified by the times.